PENGARUH PRESTASI PRAKTIK PENGALAMAN LAPANGAN (PPL), PENGUASAAN KOMPETENSI PROFESIONAL, DAN MOTIVASI MAHASISWA TERHADAP KESIAPAN MENJADI GURU MATA PELAJARAN EKONOMI/AKUNTANSI YANG PROFESIONAL (STUDI KASUS MAHASISWA PROGRAM STUDI PENDIDIKAN AKUNTANSI TA - Pratama, Bayu Rizky; Lutfiyani, Niswah; Nugrahaini, Irtifah (Jurnal Penelitian Pendidikan, 2015)
Indonesia is facing problems about the low quality of teachers. Based on early competency test performed (UKA) on candidates to be certified teachers, found low national competence of teachers with the point of 42,25. Need to be analyzed various factors causes low teacher quality, including by analyzing the prospective teachers are college graduates. In this research, tested the level of readiness of prospective teachers to become teachers professional accounting. The aim of this research is to (1) determine and analyzed the influence of achievement practice field experience (PPL) against readiness students to become teachers economic subjects/accounting that professional, (2) determine and analyzed the influence of mastery of student professional competence against readiness to become teachers economic subjects/professional accounting, (3) determine and analyzed the impact of student motivation against readiness to become teachers economic subjects/professional accounting. Research method in this research using multiple regression with a design research quantitative description. Based on t test have been made, it turns out the achievement of the practice field experience (PPL) have no influence on the readiness of becoming a teacher professional ac- counting. Did not influence the achievement of the practice field experience (PPL) caused by some things, including (1) the personal relationships with students of teachers, (2) Less attention from teacher to student were having a practice field experience (PPL), (3) To compete with students practice field experience (PPL) of other universities. As for professional competency and motivation of students having the effect on readiness to be a teacher is indicated by significance of 0,007 and 0,006. Both influential each of the 43,5% and 44,5% of readiness students to be teachers accounting in which the professional.